Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(P=\frac{3\left(x+\sqrt{x}-3\right)}{x+\sqrt{x}-2}+\frac{\sqrt{x}+3}{\sqrt{x}+2}-\frac{\sqrt{x}-2}{\sqrt{x}-1}\) \(\left(x\ge0;x\ne1\right)\)
\(P=\frac{3x+3\sqrt{x}-9}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}+\frac{\left(\sqrt{x}+3\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}-\frac{\left(\sqrt{x}-2\right)\left(\sqrt{x}+2\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(P=\frac{3x+3\sqrt{x}-9+x+2\sqrt{x}-3-x+4}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(P=\frac{3x+5\sqrt{x}-8}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(P=\frac{\left(\sqrt{x}-1\right)\left(3\sqrt{x}+8\right)}{\left(\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}\)
\(P=\frac{3\sqrt{x}+8}{\sqrt{x}+2}\)
b) \(P=\frac{7}{2}\)
\(\Leftrightarrow\frac{3\sqrt{x}+8}{\sqrt{x}+2}=\frac{7}{2}\)
\(\Rightarrow6\sqrt{x}+16=7\sqrt{x}+14\)
\(\Leftrightarrow\sqrt{x}=2\Rightarrow x=4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(\frac{x-2}{x+2\sqrt{x}}-\frac{1}{\sqrt{x}}+\frac{2}{\sqrt{x}+2}\)
\(=\frac{x-2}{x+2\sqrt{x}}-\frac{\sqrt{x}+2}{x+2\sqrt{x}}+\frac{2\sqrt{x}}{x+2\sqrt{x}}\)
\(=\frac{x+\sqrt{x}-4}{x+2\sqrt{x}}\)
b/ \(\frac{x+\sqrt{x}-4}{x+2\sqrt{x}}=\frac{4+2\sqrt{3}+\sqrt{\left(\sqrt{3}+1\right)^2}-4}{4+2\sqrt{3}+2\sqrt{\left(\sqrt{3}+1\right)^2}}\)
\(=\frac{4+2\sqrt{3}+\sqrt{3}+1-4}{4+2\sqrt{3}+2\sqrt{3}+2}=\frac{1+3\sqrt{3}}{6+4\sqrt{3}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(ĐKXĐ:x>0;x\ne4\)
Ta có : \(P=\left(\frac{\sqrt{x}}{\sqrt{x}-2}+\frac{4x}{2\sqrt{x}-x}\right):\left(\frac{\sqrt{x}+3}{\sqrt{x}-2}\right)\)
\(=\left[\frac{\sqrt{x}.\sqrt{x}-4x}{\sqrt{x}.\left(\sqrt{x}-2\right)}\right]\cdot\frac{\sqrt{x}-2}{\sqrt{x}+3}\)
\(=\frac{-3x}{\sqrt{x}.\left(\sqrt{x}+3\right)}\)
b) Ta có : \(x-1=10-4\sqrt{6}=\left(\sqrt{6}-2\right)^2\)
\(\Rightarrow\sqrt{x}=\sqrt{\left(\sqrt{6}-2\right)^2+1}\)
......
Rút gọn : \(Q=\frac{4x+17\sqrt{x}+4}{2x+7\sqrt{x}-4}\) (ĐK : \(0\le x\ne\frac{1}{4}\))
\(=\frac{\left(\sqrt{x}+4\right)\left(4\sqrt{x}+1\right)}{\left(2\sqrt{x}-1\right)\left(\sqrt{x}+4\right)}=\frac{4\sqrt{x}+1}{2\sqrt{x}-1}\)
\(Q\in Z\Leftrightarrow\frac{4\sqrt{x}+1}{2\sqrt{x}-1}\in Z\Leftrightarrow2+\frac{3}{2\sqrt{x}-1}\in Z\Leftrightarrow\frac{3}{2\sqrt{x}-1}\in Z\Rightarrow\left(2\sqrt{x}-1\right)\inƯ\left(3\right)\)
Do \(x\ge0\)nên \(2\sqrt{x}-1\ge-1\Rightarrow\left(2\sqrt{x}-1\right)\in\left\{-1;1;3\right\}\Leftrightarrow x\in\left\{0;1;4\right\}\)